2023
DOI: 10.3389/fsurg.2023.1071259
|View full text |Cite
|
Sign up to set email alerts
|

Development of prognostic indicator based on NAD+ metabolism related genes in glioma

Abstract: BackgroundStudies have shown that Nicotinamide adenine dinucleotide (NAD+) metabolism can promote the occurrence and development of glioma. However, the specific effects and mechanisms of NAD+ metabolism in glioma are unclear and there were no systematic researches about NAD+ metabolism related genes to predict the survival of patients with glioma.MethodsThe research was performed based on expression data of glioma cases in the Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) databases. Firstl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Consequently, we recognize the importance of NAM metabolism in tumor prognosis and immunity and its potential value as a prognostic indicator. Although Jiang C et al and Jiang C et al investigated the relationship between NAD + metabolism and the progression and prognosis of patients with glioma, these studies only constructed a simple survival risk model [12,13] . They did not perform multi-level bioinformatics analysis, clarify the role of key genes in signaling pathways, or examine the immune environment.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we recognize the importance of NAM metabolism in tumor prognosis and immunity and its potential value as a prognostic indicator. Although Jiang C et al and Jiang C et al investigated the relationship between NAD + metabolism and the progression and prognosis of patients with glioma, these studies only constructed a simple survival risk model [12,13] . They did not perform multi-level bioinformatics analysis, clarify the role of key genes in signaling pathways, or examine the immune environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nurse-like cells cloned from bone marrow and synovial tissues of patients with rheumatoid arthritis promoted survival of peripheral B cells, which was significantly blocked by anti-BST-1/CD157 antibody; and recombinant soluble BST-1/CD157 showed a similar survival effect ( 2 , 22 ). It has been also demonstrated that BST-1/CD157 is involved in the progression and differentiation of leukemia ( 23 25 ), metastasis of ovarian carcinoma cells ( 26 28 ), malignant mesothelioma ( 29 , 30 ) and glioma ( 31 ), and thus could be used as diagnostic or prognostic markers. Particularly, BST-1/CD157 has been regarded as a target for immunotherapy of acute myeloid leukemia ( 23 25 ).…”
Section: Introductionmentioning
confidence: 99%